2014
DOI: 10.1111/ele.12381
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity predicts beta but not alpha diversity of soil microbes across grasslands worldwide

Abstract: Aboveground-belowground interactions exert critical controls on the composition and function of terrestrial ecosystems, yet the fundamental relationships between plant diversity and soil microbial diversity remain elusive. Theory predicts predominantly positive associations but tests within single sites have shown variable relationships, and associations between plant and microbial diversity across broad spatial scales remain largely unexplored. We compared the diversity of plant, bacterial, archaeal and funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

71
452
16
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 625 publications
(576 citation statements)
references
References 47 publications
71
452
16
4
Order By: Relevance
“…On the other hand, it was suggested in this study that soil bacterial species diversity (α-diversity) was not strongly influenced by aboveground forest type (Tables 3 and 4c). These results may be relevant to the finding from a study on temperate grassland sites that aboveground plant α-diversity can predict patterns of belowground soil bacterial composition (β-diversity) but not the pattern of α-diversity (Prober et al, 2015). However, since a diverse range of aboveground forest types was investigated in this study, it is reasonable to assume that many different factors other than plant α-diversity might have contributed to our results.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…On the other hand, it was suggested in this study that soil bacterial species diversity (α-diversity) was not strongly influenced by aboveground forest type (Tables 3 and 4c). These results may be relevant to the finding from a study on temperate grassland sites that aboveground plant α-diversity can predict patterns of belowground soil bacterial composition (β-diversity) but not the pattern of α-diversity (Prober et al, 2015). However, since a diverse range of aboveground forest types was investigated in this study, it is reasonable to assume that many different factors other than plant α-diversity might have contributed to our results.…”
Section: Discussionsupporting
confidence: 48%
“…On the other hand, subtropical soils in Brazil and Florida and temperate soils in Illinois and Canada were comparable with respect to the level of soil bacterial diversity (10 4 species per sample), based on pyrosequencing analyses of the 16S rRNA region (Roesch et al, 2007). Recently, by studying 25 temperate grassland sites from four continents (Africa, Australia, Europe and North America) by high-throughput sequencing of 16S rRNA (bacteria and archaea) and an ITS region (fungi), it was shown that plant α-diversity was poorly related to that for microbial groups (Prober et al, 2015). In our previous work on five tropical forests in Malaysia and one temperate forest in Japan, using pyrosequencing analy-ses of bacterial 16S rRNA (Miyashita et al, 2013), we also observed a similar composition of higher taxonomic taxa and similar bacterial species diversity in the six forests.…”
Section: Introductionmentioning
confidence: 99%
“…Details of this data set and the methods used to characterize the bacterial and fungal communities are available in Prober et al (2015). In total, 37 393 ITS fungal operational taxonomic units (OTUs) and 223 693 16S rRNA bacterial OTUs (with OTUs defined at 497% sequence similarity level for ITS1 and 16S rRNA reads for fungi and bacteria, respectively) were included to the analysis.…”
Section: Co-occurrence Analysismentioning
confidence: 99%
“…Similar to previous work (Wardle, 2006; Prober et al., 2014; e.g., Fierer & Jackson, 2006), microbial diversity did not respond to experimental plant treatments. The lack of soil effect here, which contradicts findings elsewhere (Fierer & Jackson, 2006), may be due to the relatively small experimental effects on pH relative to intersite variation.…”
Section: Discussionmentioning
confidence: 98%
“…Alpha diversity of soil bacteria has been associated with edaphic conditions, most notably pH (Fierer & Jackson, 2006), but not plant diversity or composition (Fierer & Jackson, 2006; Prober et al., 2014; Wardle, 2006). The evidence for other predicted diversity relationships is more mixed, for example, elevational gradients have been observed (Bryant et al., 2008) and not observed (Fierer et al., 2011).…”
Section: Introductionmentioning
confidence: 99%